Intraoperative lagophthalmos formula for levator resection in congenital ptosis. Issue 6 (26th July 2018) - Kang, Sunah; Seo, Ji Won; Ahn, Chan Joo; Esmaeli, Bita; Sa, Ho-Seok
Abstract : Aim: To calculate a regression formula for intraoperative lagophthalmos to determine the amount of correction in levator resection for mild to moderate congenital ptosis. Methods: This retrospective study included 38 eyelids from 28 consecutive children with congenital ptosis with levator function of 4 mm or better who showed satisfactory surgical outcomes defined as postoperative margin reflex distance-1 (MRD1) ≥3 mm in each eye and difference in MRD1 ≤1 mm between eyes at 6 months after levator resection. We investigated whether the degree of intraoperative lagophthalmos measured by calliper correlated with the preoperative values of MRD1, levator function and age. A stepwise multiple regression analysis was performed with intraoperative lagophthalmos as the dependent variable. Results: The mean intraoperative lagophthalmos was 7.4±0.9 mm (range, 6–10 mm). The intraoperative lagophthalmos was found to have a statistically significant negative correlation with preoperative MRD1 ( r 2 =0.55, p<0.0001) and levator function ( r 2 =0.53, p<0.0001), respectively. A stepwise multiple regression analysis resulted in the following regression formula: Intraoperative lagophthalmos=9.08 – 0.48×Preoperative MRD1 – 0.26×Levator function ( r 2 =0.60, p<0.0001). Conclusion: Intraoperative lagophthalmos in patients with satisfactory surgical outcome correlated negatively with both preoperative MRD1 and levator function and accounting for both variables resulted in a stronger correlation than either variable alone. Surgeons would be able to calculate the amount of surgical correction using this formula of intraoperative lagophthalmos, which could lead to a satisfactory surgical outcome in levator resection for congenital ptosis.